Utilizing a Circular Economy in Household Waste Management MSMEs: A Case Study of Innovation in a Small Town - Dwi Narsih; Meirinaldi (Greenation International Journal of Economics and Accounting, 2025)
Circular economy has become an alternative model in addressing household waste problems through the development of SMEs in small cities. This research analyzes the implementation of circular economy concepts in household waste processing SMEs with case studies in three small cities in Central Java. Qualitative methods with a case study approach were used to collect data through interviews and observations of 15 waste banks and waste processing SMEs. The results showed that the implementation of a circular economy in SMEs resulted in an average income increase of 45% in the 2022-2024 period and waste volume reduction of up to 60%. The business models developed include collection, sorting, processing, and marketing of recycled products. However, constraints were found in terms of access to capital, technology, and marketing. This research provides theoretical contributions in developing small-scale circular economy models and policy recommendations to support waste management SMEs.